Bankruptcy Risk Diagnostics Model for Aviation Enterprises - Василий Юрьевич Жданов; Ольга Анатольевна Афанасьева (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2012)
Authors: Vasily Y. Zhdanov - National Research University "Higher School of Economics"Olga Anatolievna AfanasyevaThe article deals with the disadvantages of using foreign models of the bankruptcy risk diagnostic to forecast the bankruptcy risk of aviation companies. The advantages of using logistic regression models (logit-model) are justified compared with the models constructed using multiple discriminant analysis (MDA-model). Logit-model is developed for diagnosing the bankruptcy risk of aviation companies.